Optimizing transformational leadership and knowledge management as keys to innovation - Prawira Negara, Arif Bijaksana; Pradana, Mahir; Silvianita, Anita; Rubiyanti, Nurafni; Madiawati, Putu Nina; Nabila, Farizka Shafa (Journal of Infrastructure, Policy and Development, 2024)
This report intends to enhance the reviews on leadership literature by conducting a bibliometric study on 198 publications focused on transformational leadership research. These papers were published in the Scopus database between 1997 and 2023. Employing quantitative bibliometric analysis, the study aims to identify both current and prospective research trajectories pertaining to transformational leadership issues. To the best of our current understanding, there exists no scholarly investigation that examines the bibliographic data pertaining to transformational leadership domains. Therefore, this work represents a distinctive and original contribution to the existing body of literature. This study additionally offers a comprehensive examination of the patterns and paths inside a visual and schematic framework for the investigation of this subject matter. This may facilitate researchers in comprehending the prevailing patterns and prospective avenues for research, so empowering future authors to carry out their investigations with greater efficacy. There exists a number of underexplored themes or subjects pertaining to transformational leadership matters, such as knowledge sharing, leadership styles, digital transformation, innovative work behavior, competitive advantage and digital transformation. This discovery offers useful insights into the heterogeneous nature of this area across multiple disciplines.